2013
DOI: 10.1007/s00380-013-0327-0
|View full text |Cite
|
Sign up to set email alerts
|

Zotarolimus-eluting stent utilization in small-vessel coronary artery disease (ZEUS)

Abstract: The role of the second-generation zotarolimus-eluting stent RESOLUTE in small-vessel coronary artery disease is unclear. The aim of this study was examine the angiographic results of RESOLUTE in de novo coronary lesions of ≥50 % diameter stenosis in target vessels ≤2.5 mm. From August 2008 to April 2010, 142 symptomatic patients with 159 lesions who fitted the inclusion criteria were treated with RESOLUTE. The mean age of patients was 66 ± 10 years, with male predominance (66 %). Diabetes mellitus was found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The R-ZES is a second-generation device that has been studied in international small vessel trials. 8,18 Caputo et al 8 showed that the 2-year clinical outcomes after implantation of the second-generation R-ZES in patients with small vessels were similar to those in patients with larger vessels. There was no significant difference in target lesion failure (10.1% vs 8.7%; P = .54) at 2 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The R-ZES is a second-generation device that has been studied in international small vessel trials. 8,18 Caputo et al 8 showed that the 2-year clinical outcomes after implantation of the second-generation R-ZES in patients with small vessels were similar to those in patients with larger vessels. There was no significant difference in target lesion failure (10.1% vs 8.7%; P = .54) at 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…Angiographic restenosis was found in 9 (6.3%) lesions, and the rate of major adverse cardiac events was 8.5%. 18 More recently, the ENDEA-VOR IV randomized controlled trial (of the Medtronic Endeavor Drug [ABT-578] Eluting Coronary Stent System Versus the Taxus Paclitaxel-Eluting Coronary Stent System in De Novo Native Coronary Artery Lesions), 19 which assessed the outcomes after implantation of E-ZES and PES in patients with single de novo coronary lesions, showed that E-ZES and PES were associated with similar TLR (7.7% vs 8.6%, P ¼ .70) and TVR (17.2% vs 21.1%, P ¼ .061) rates; however, the incidence of cardiac death or MI was lower with E-ZES (6.4% vs 9.1%, P ¼ 0.048), primarily driven by a lower rate of target vessel MI with E-ZES (2.6% vs. 6.0%, P ¼ .002). Although overall definite/probable stent thrombosis rates were similar between stents (1.3% vs 2%, p ¼ 0.42), rates of very late stent thrombosis (0.4% vs. 1.8%, P ¼ .012) and late MI events (1.3% vs. 3.5%, P ¼ .008) were significantly lower with E-ZES compared with PES.…”
Section: Discussionmentioning
confidence: 99%
“…Promising results have been shown of DCB in the intervention of SVD, in-stent restenosis (ISR), and some other special coronary lesions. The PEPCAD I study [13,33] was the rst trial to assess the performance of a DCB in a high risk patient population with small coronary vessel disease, one hundred and eighteen patients with a target vessel diameter of 2.25-2.8 mm were treated by paclitaxel coated balloons (PCB), LLL in the 6 month angiographic follow-up and MACE rate in the 12 month clinical follow-up are both promising and are not inferior to the results of DES for SVD reported by other studies [34][35][36][37][38]. In BELLO study [17], which is the rst long-term follow-up RCT comparing PCB with paclitaxel eluting stent for SVD, PCB showed signi cant lower LLL in the 6 month angiographic follow-up and a tendency towards lower incidence of MACE during 2 year clinical follow-up compared to DES.…”
Section: Ptca Of Small Vessel Disease With Plain Balloon Angioplastymentioning
confidence: 95%
“…Koning et al [3] showed that 6Fr and 7Fr Mallinckrodt Softouch catheters satisfy the acceptance criteria for QCA calibration procedures, in that the average difference between the angiographically measured and true diameters is smaller than 3.5 % and the pooled standards of the measured diameters are on the order of 0.1 mm or lower [4]. Accurate and precise QCA analysis is necessary in evaluating acute gain and late loss after percutaneous coronary intervention (PCI) [5], or disease progression [6,7] especially in multicenter trials [8]. However, the Abstract To evaluate the feasibility of catheter down sizing for QCA, the reliability of a 4Fr catheter as a calibration device was evaluated.…”
Section: Introductionmentioning
confidence: 98%